Justification of parameters artificial soil for laboratory research of cutting edge wear - I. V. Liskin; D. A. Mironov; R. K. Kurbanov (Сельскохозяйственные машины и технологии)
For soil cultivation with the cutting tools of agricultural machines we can allocate three main types of shavings: shift, separation and continuous chip. The shift is most accurately expressed on sandy soils, a separation - on clay and loamy, continuous chip - on humid soils with the high content of clay particles. In field conditions researches of regularities of cutting edges wear are complicated because of heterogeneity of physic and mechanical properties of the soil and the changing climatic conditions. At laboratory modeling of soil conditions we can make experiments independent of weather and season. For development of the artificial soil and depend modeling of edges wear we considered conditions of creation of model with use mechanics of abrasive wear. Have allocated The major factors defining character and intensity of wear were allocated. The wearing-out ability of abrasive particles is defined by the radius of the curve of their sharp ledges. This radius depends on the particle size. The hardness of the soil influences wear of the cutting details and characterizes penetration into it of the cutting elements, and degree of fixedness of abrasive particles defines shaving type. We conseeder the soil as the abrasive environment with the particles which are in a condition of non-rigid fixing and have an opportunity to move relatively each other or to turn on itself under the influence of normal and tangential stress. Type of shaving when soil layer destruction depends on a ratio of the normal and tangential stress characterizing degree of fixedness of firm particles. We conducted researches of physic and mechanical properties of the artificial soil on the basis of quartz sand and paraffin. Injection of the petrolatum into structure of the artificial soil reduces the hardness and degree of fixedness of firm particles, but the ceresin increases these indicators. The mechanical structure was changed due to introduction of dust-like cement and replacement of fractions of abrasive particles. We manufactured blocks of the artificial soil, melting paraffin at a temperature of 85-90 degrees Celsius and filling up in it a firm phase. Researches make it possible to choose options of the artificial soil for studying of the main regularities of soil cutting elements.